A Common Fixed Point Theorem for Gregus Type Mappings: S.D. Diwan, Rajlaxmi Gupta - Team, Support (Thai Journal of Mathematics, 2014)
In this paper, we establish a common fixed point theorem for Gregus type mappings in metric spaces using the (CLRg) property. Our result generalizes and improves upon, among others the corresponding results of Gregus [1], Fisher and Sessa [2], Huang and Cho [3], Jungck[4], Ciric [5] and Mukherjee and Verma [6].